PENYULUHAN BAHAYA MEROKOK DALAM RANGKA PERINGATAN HARI PENYAKIT PARU OBSTRUKTIF KRONIK (PPOK) SEDUNIA DAN BULAN PEDULI KANKER PARU - Russilawati Russilawati; Sabrina Ermayanti; Masrul Basyar (LOGISTA - Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Padang Municipality has been making effort to improve quality of life for its citizens by providing out door facility trough weekly car free day program. Even though it is supposed to be fresh air there were many visitors still smoking tobacco so that caused air pollution. Tobacco smoking has been known as major risk factor for Chronic Obstructive Pulmonary Disease (COPD) and lung cancer. In addition tobacco smoking has been considered to have association with twenty millions premature deaths. Our objectives were to outspread knowledge about hazard of tobacco and smoking cessation campaign in commemoration of COPD word day and month of lung cancer care 2018. Counseling was implemented by presentation, discussion, leaflet, and quiz with door prize. Meanwhile, smoking cessation campaign was performed by waking around and giving present to individu who willingly put out the cigarette at the moment. Total 155 visitors were involved in the event. They were classified in three groups of never smoker, former smoker or current smoker. Furthermore, 74 self identified current smokers were assessed in regard of grade of smoking, nicotine dependence, and motivation to smoke by using standardized questioner. Analysis of interview found out most of visitors were mild smoker with low nicotine dependence, and had motivation for smoking by social influence and stress relief. The data could be considered in choosing smoking cessation program for community. Keyword: tobacco smoking, nicotine, COPD, lung cancer